{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# sol11 - CS 70 Fall 2006 — Solutions to Homework#11 1...

This preview shows pages 1–2. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: CS 70 Fall 2006 — Solutions to Homework #11 November 30, 2006 1. Machine Failures. We have that X 1 ∼ Geometric ( p 1 ) , X 2 ∼ Geometric ( p 2 ) are the independent r.v.’s representing the number of runs until the first failure for machines M 1 and M 2 respectively. If X = min { X 1 , X 2 } then for x ∈ { 1 , 2 , . . . } Pr ( X ≥ x ) = Pr (min { X 1 , X 2 } ≥ x ) = Pr (( X 1 ≥ x ) ∧ ( X 2 ≥ x )) = Pr ( X 1 ≥ x ) · Pr ( X 2 ≥ x ) , by the independence of X 1 and X 2 = (1- p 1 ) x- 1 (1- p 2 ) x- 1 , by the tail probability of a Geometric [see Thm 21.2 part (2)] = ((1- p 1 ) (1- p 2 )) x- 1 = (1- p 1- p 2 + p 1 p 2 ) x- 1 This is the tail probability of a Geometric with parameter p 1 + p 2- p 1 p 2 and since X ∈ { 1 , 2 , . . . } is the support of a Geometric r.v. it must be that X ∼ Geometric ( p 1 + p 2- p 1 p 2 ) as claimed. 2. Geometric Distribution. Let T be the total number of attempts Mr. Bond must make before he escapes from his imprisonment. I.e. the first T- 1 attempts are failures—where he either enters the AC duct or the sewer pipe—and the final attempt at trial T seems him enter the door. Thus T corresponds to the number of coin tosses landing tails until a head turns up, where a tail (Bond fails) comes up with probability 2 / 3 while a head (007 escapes) has probability 1 / 3. Hence T ∼ Geometric (1 / 3). Define X t for t ∈ { 1 , 2 , . . . , T- 1 } to be the time Bond spends on failed trial t . Then X the total time Bond spends trying to escape is a r.v. satisfying X = T- 1 X t =1 X t Clearly the failure trial times X 1 , . . . , X T- 1 are i.i.d. with distribution X t = ( 2 with probability 0 . 5 5 with probability 0 . 5 and so E [ X 1 ] = . . . = E [ X T- 1 ] = 2 · Pr ( X t = 2) + 0...
View Full Document

{[ snackBarMessage ]}

### Page1 / 5

sol11 - CS 70 Fall 2006 — Solutions to Homework#11 1...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online